Editorial of Special Issue “Oral Cancer: From Pathophysiology to Novel Therapeutic Approaches” - Vui King Vincent-Chong (Biomedicines, 2023)
Oral squamous cell carcinoma (OSCC) is a heterogeneous type of malignancy that develops within the oral cavity comprising the lips, tongue, mouth floor, gums, and buccal mucosa, with more than 90% arising from the oral lining epithelium [...]